Therapeutic apheresis in the complex pathogenetic therapy of anti-NMDA encephalitis associated with ovarian teratoma at a late stage of the disease - S. N. Bardakov; D. I. Skulyabin; A. N. Moshnikova; S. V. Lapin; A. A. Sokolov; E. A. Kondratyeva; T. V. Bulgakova; A. S. Manuilov; M. V. Zakharov; A. N. Belskikh; V. A. Tsargush; R. V. Deev (Нервно-мышечные болезни)
Anti‑NMDA encephalitis is a rare autoimmune disease of the central nervous system caused by the synthesis of autoantibodies to the NR1/NR2 subunits of the NMDA receptor, characterized by the development of acute mental, cognitive, motor, autonomic disorders, epileptic syndrome and central hypoventilation.The article presents a three‑year observation of patient 34 years old with anti‑NMDA ncephalitis associated with late‑ stage ovarian teratoma, accompanied by an increase titer of antibodies to NMDA receptors in serum to 1:640.Based on a detailed analysis of clinical, neurological, neuropsychological (MMSE, MoСA, FAB, 10 words test A.R. Luria) and laboratory‑instrumental characteristics of the disease (titer anti‑NMDA, level of IgG, IgM, IgA, lymphocyte subpopulations, EEG, MRI of the brain, pelvis) suggested a combination scheme of first and second line therapy. The sequential use of two cycles of medium‑volume membrane plasmapheresis (25–30 % of the circulating plasma volume, No. 5 + 5) was carried out in combination with pulse therapy with methylprednisolone 1.0 (No. 4 + 3) and cyclophasphamide 1.0 (No. 2 + 1) on background of persistent ovarian teratoma. Symptom regression was achieved by the end of the first cycle, and full recovery to the initial level of cognitive functions occurred after the second cycle, while maintaining the anti‑NMDA antibody titer to 1:160. After removal of ovarian teratoma, the level of anti‑NMDA decreased in a month to 1:40, and after 7 months it reached normal values (<1:10) against the background of basic pill therapy with methotrexate 12.5 mg/week.Thus, a rational combination and sequence of first and second line therapy and therapeutic apheresis, taking into account the pathogenetic features of each phase of the disease, can quickly achieve complete stable remission in patient with anti‑NMDA encephalitis.